1994
DOI: 10.2214/ajr.163.3.8079858
|View full text |Cite
|
Sign up to set email alerts
|

Detection and staging of chondromalacia patellae: relative efficacies of conventional MR imaging, MR arthrography, and CT arthrography.

Abstract: OBJECTIVE.Chondromalacia patellae is a condition characterized by softening, fraying, and ulceration of patellar articular cartilage. We compare the sensitivity, specificity, and accuracy of conventional MR imaging, MR arthrography, and CT arthrography in detecting and staging this abnormality. SUBJECTS AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(94 citation statements)
references
References 0 publications
4
85
0
5
Order By: Relevance
“…The role of MR imaging in inflammatory arthropathy has not been reviewed in detail for this article. A good correlation between grading of cartilage lesions at MR imaging and grading at arthroscopy has been shown for chondromalacia patellae (5, 13,36,44), osteochondritis dissecans (9, 27) and osteoarthrosis (4) but as a common finding there was best correlation for the higher grade lesions. This suggests that MR may able to select the patients with more advanced cartilage lesions who require further treatment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The role of MR imaging in inflammatory arthropathy has not been reviewed in detail for this article. A good correlation between grading of cartilage lesions at MR imaging and grading at arthroscopy has been shown for chondromalacia patellae (5, 13,36,44), osteochondritis dissecans (9, 27) and osteoarthrosis (4) but as a common finding there was best correlation for the higher grade lesions. This suggests that MR may able to select the patients with more advanced cartilage lesions who require further treatment.…”
Section: Discussionmentioning
confidence: 88%
“…The data from reviewed studies are summarised in Table 4 which also includes studies with less than 40 patients. The comparative studies (3, 5, 8, 13,18,19,36,41) provide complete or partial data regarding sensitivity, specificity, positive and negative predictive values and accuracy of MR. The results concerning the ability of MR to detect articular cartilage lesions are quite confusing.…”
Section: Discussionmentioning
confidence: 99%
“…Grade I lesions were excluded as a result of the difficulties in differentiating these lesions from normal (ICRS Grade 0) cartilage by MRI [9]. Because previous studies have shown MRI is unreliable in detecting superficial lesions (softening) [13,16,27], only Graded II to IV lesions were documented to avoid false-positive MRI findings. ICRS Grade II describes articular cartilage defects extending down to less than 50% of cartilage depth, Grade III extending deeper than 50% of cartilage depth, and Grade IV are defects with full-thickness articular cartilage loss.…”
Section: Methodsmentioning
confidence: 99%
“…MR arthrography seems to be superior to standard MRI in the detection of cartilage lesions at the knee especially for early lesions. But again MR arthrography is not perfect with reported sensitivities in detecting grade 1 lesions at the patellar cartilage ranging from 29 to 53% [5,6]. To be able to benefit from the advantages of MR arthrography it is essential that enough contrast material enters between the articular surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…MR arthrography also has the potential to identify intra-articular bodies [4], and chondral [5,6] and osteochondral [7] lesions and is helpful after reconstruction of the anterior cruciate ligament [8].…”
Section: Introductionmentioning
confidence: 99%